Evaluation of Technical Assistance to Post-Conflict Countries-Mozambique and Rwanda. (Policy Papers; Policy Paper ;, 2009)
This evaluation of technical assistance (TA) in statistics covers two post-conflict countries, namely, Mozambique and Rwanda during the period 2000-08. The TA, including training, covered the broad spectrum of the Statistics Department's (STA) program, including collaboration with the East Africa Regional Technical Assistance Center (East AFRITAC), the U. K. Department for International Development (DFID), and the Japanese-funded General Data Dissemination System (GDDS) projects, as well as TA funded directly from the IMF's budget. The emerging lessons also provide a useful guide to future TA to non-English-speaking countries. The evaluation is based on missions to each country and relied on responses to questionnaires, desk reviews of available data, and discussions with country authorities, donors, data users, and national officials who participated in IMF courses in statistics.